A comparative immunohistochemical and immunophenotypical study on lymphocytes expression in patients affected by oral lichen planus. (17th March 2013) - Lorenzini, Guido; Viviano, Massimo; Chisci, Elettra; Chisci, Glauco; Picciotti, Maria
<x xml:space="preserve">Abstract</x> Background Oral lichen planus (OLP) is an immune‐mediated mucocutaneous disease of uncertain aetiology. OLP has many manifestations: reticular, erosive, atrophic, plaque like, papular, bullous, with unique etiopathogenetic working. The purpose of this study is to find a link between different clinical types of lichen and the alterations of lymphocytes on peripheral blood and oral mucosa. Materials and Methods A total of 21 patients were enrolled in this study. The mean age of patients was 53.82 years, between 31 and 78 years. OLP Diagnosis was afterwards confirmed by histopathology. Selected patients underwent to clinical evaluation, lesion characterization, incisional biopsy, samples histological analysis, peripheral blood collection. Blood specimens were submitted to cell count determination with differential, characterization of populations and circulating lymphocyte subpopulations using monoclonal antibodies in flow cytometry. Referring to the clinical presentation of lesions, patients were divided in two groups: red lesions (RL) and white lesions (WL) and compared with an age‐matched control group. Results The results of the immunophenotypic study showed correlation between WL and the expression of CD19 lymphocytes (r = 0.693, P = 0.0005). The results of immunohistochemical study performed on histological specimens showed a significant correlation between RL group and expression of all lymphocyte tested (CD3 r = 0.722 P = 0.0002, CD4 r = 0.579 P = 0.0060, CD56 r = 0.513 P = 0.0173, CD8 r = 0.548 P = 0.0102). Conclusions We assume there is the responsibility of the expression of lymphocytes, not only type but also as quantity, in determining RL or WL manifestation of OLP. Circulating lymphocytes may have a role, too.